2016
DOI: 10.1021/acs.langmuir.6b01621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ROS Produced by Nanobubbles and Their Positive and Negative Effects on Vegetable Seed Germination

Abstract: Exogenous reactive oxygen species (ROS) produced by nanobubble (NB) water offer a reasonable explanation for NBs' physiological promotion and oxidation effects. To develop and exploit the NB technology, we have performed further research to identify the specific ROS produced by NBs. Using a fluorescent reagent APF, a Fenton reaction, a dismutation reaction of superoxide dismutase and DMSO, we distinguished four types of ROS (superoxide anion radical (O·), hydrogen peroxide (HO), hydroxyl radical (·OH), and sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 40 publications
3
170
1
2
Order By: Relevance
“…As plant cell walls determine shape and the rate and direction of growth of individual cells as well as the mechanical resistance of whole tissues, the loosening of cell walls is an important process in all stages of plant development, requiring elongation growth or tissue weakening 77 . It has been approved that ROS, including •OH can act as a key component in cell wall loosening, testa and endosperm weakening, which is essential for radicle protrusion in seed germination 77 79 . As observed by ESR technique, AgNPs could mediate the generation of •OH, and thus act as ROS-generating agent.…”
Section: Discussionmentioning
confidence: 99%
“…As plant cell walls determine shape and the rate and direction of growth of individual cells as well as the mechanical resistance of whole tissues, the loosening of cell walls is an important process in all stages of plant development, requiring elongation growth or tissue weakening 77 . It has been approved that ROS, including •OH can act as a key component in cell wall loosening, testa and endosperm weakening, which is essential for radicle protrusion in seed germination 77 79 . As observed by ESR technique, AgNPs could mediate the generation of •OH, and thus act as ROS-generating agent.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the likelihood of this hypothesis is underlined by several indications found in literature. For instance, aqueous nanobubble solutions produce hydroxyl radicals, 354,355 which makes them interesting for water treatment (see Refs. 190 and 192 for two reviews) and agricultural applications.…”
Section: B Surface Ion Release: Surfing On Capillary Waves and Taylomentioning
confidence: 99%
“…Indeed, experimental studies have shown the growth promotion of plants, fish, and mice by nanobubbles. [354][355][356] Both applications are reminiscent of the observed effects induced by plasma treated solutions. 357,358 Figure 27, for instance, draws an analogy between the favorable long-term effect of plasma treated water and nanobubble solution as fertilizer on the growth of plants.…”
Section: B Surface Ion Release: Surfing On Capillary Waves and Taylomentioning
confidence: 99%
“…Palladium electrode with ultrasonication has been used to form nanobubbles of 300-500 nm diameter [23]. Nanobubbles form reactive free radicals as they collapse due to the presence of ions in groups at the gas-liquid interface [24]. The ability of nanobubbles to form reactive free radicals makes them potent applicants in the field of pre-treatment of wastewater components.…”
Section: Nanobubblesmentioning
confidence: 99%